PENERAPAN STRATEGI PEMBELAJARAN AKTIF TIPE PREDICT-OBSERVE-EXPLAIN (POE) UNTUK MENINGKATKAN PRESTASI BELAJAR PESERTA DIDIK PADA POKOK BAHASAN KOLOID DI KELAS XI MIA SMA NEGERI 1 PEKANBARU - Nurlaili Qodriyah; Maria Erna; Roza Linda (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The research about implementation active learning Predict-Observe-Explain (POE) strategy to improve students learning achievement on the colloid subject at the class XI MIA SMAN 1 Pekanbaru have been done. The research was a form of experimental research with the design Randomized Control Group Pretest-Posttest. The sample consists of two classes, class XI MIA 9 as the experimental class and class XI MIA 5 as the control class is determined randomly after normality test and homogeneity test. Experimental class was implied of active learning Predict-Observe-Explain (POE) strategy while the control class didn’t imply of active learning Predict-Observe-Explain (POE) strategy. Data analysis technique used is the t-test. Based on the results of data processing obtained tcount > ttable is 3,47 > 1,67, its means that the implementation of active learning Predict-Observe-Explain (POE) strategy can improve students learning achievement on the colloid subject at the class XI MIA SMAN 1 Pekanbaru. Categories of learning achievement of student amount 0,80 with the high categories.Key words: Active Learning Predict-Observe-Explain (POE) Strategy, Learning Achievement, Colloid